Peran Public Relations PT. KCIC dalam Membangun Brand Awarenees Kereta Cepat Whoosh - Maulidina Wamareta Putri; Winda Dwi Astuti Zebua (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
PT. The Indonesian China Fast Train is one of the companies operating in the field of public transportation services under the auspices of the government which was inaugurated directly by the President of Indonesia, namely Mr. Jokowi, who collaborates directly with China. This research aims at the Role of Public Relations Expert Prescriber PT. KCIC in building Brand Awareness for the Fast Train whoosh, the Role of Public Relations PT. KCIC as Communication Facilitator in building Brand Awareness regarding the Whoosh Fast Train, Role of Public Relations PT. KCIC in Communication Technician to build Brand Awareness of the Whoosh Fast Train, the Role of Public Relations as a Problem Solving Facilitator in handling the issue of the Whoosh Fast Train